The role of racial discrimination in medical care: A secondary analysis of the effect of culturally tailored, internet‐delivered CBT for insomnia in Black women. - Daniel, Katharine E.; Volpe, Vanessa V.; Bethea, Traci N.; Rosenberg, Lynn; Ritterband, Lee M.; Zhou, Eric S. (British Journal of Clinical Psychology, 2026)
Objectives: Prior experiences of medical racism harm health outcomes through reduced trust in medical recommendations and ultimately reduced treatment uptake. Unfortunately, experiencing medical racism is common among Black women. Culturally tailoring interventions can increase patient trust and treatment engagement. This secondary analysis examines the role of medical racism as a moderator of intervention use and sleep outcomes among Black women randomized to a tailored or standard internet insomnia treatment. Design: Secondary analysis of a randomized clinical trial. Methods: In total, 218 Black women with insomnia were randomized to tailored or standard internet insomnia treatment. Univariate linear mixed‐effects models tested whether prior medical racism moderated the effect of intervention condition on changes in sleep outcomes (ISI, PSQI, WASO, SOL) across baseline, post‐intervention and 6‐month follow‐up assessments. Binary logistic regression assessed moderation effects on remitter, responder and treatment completer status at post‐intervention. Quasi‐Poisson regression examined moderation effects on the number of program logins and sleep diaries completed. Results: Thirty‐eight per cent of participants reported prior medical racism. Medical racism did not explain differences in rates of intervention use or sleep outcomes. Insomnia symptoms comparably improved in both conditions (ps <.001). Conclusions: Over one third of the sample reported medical racism, suggesting it is not a rare occurrence for Black women; however, medical racism was not associated with intervention engagement and sleep health outcomes. Confronting racism within health care systems and providers remains necessary to promote physical and mental health equity.